Multivariate analysis of glycosylated haemoglobin in insulin-treated diabetics. - Child, D F (1985)
Glycosylated haemoglobin (HbA1), as an assessment of overall control, was estimated in 858 insulin-treated diabetics attending for changeover to U100 insulin in North East Wales. Details of age, sex, duration of diabetes, insulin regimen and monitoring method were recorded. Multivariate analysis revealed lower HbA1 in patients receiving twice-daily (mean 11.01) as compared with once-daily insulin (11.42, P = 0.011), but no difference was found between urine and blood glucose testers when other variables were taken into consideration. HbA1 was lower in men (mean 10.94) compared with women (mean 11.39, P = 0.004) and there was a positive correlation of HbA1 in men with age (P = 0.046) and in women with duration of disease (P = 0.005).